2019
DOI: 10.1007/s00167-019-05453-y
|View full text |Cite
|
Sign up to set email alerts
|

The increasing incidence of surgically treated quadriceps tendon ruptures

Abstract: PurposeDue to increased life expectancy and a more active life style of the older people, we hypothesised that the incidence of quadriceps tendon rupture (QTR) is higher than previously reported. The objective of this nationwide population-based study was to investigate the annual incidence of QTR in patients who underwent operative treatment in Finland between 1997 and 2014.MethodsThe Finnish National Hospital Discharge Register was searched for all adult patients who had undergone surgical treatment for QTR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 22 publications
0
24
1
Order By: Relevance
“…The delay between the injury and surgery was a mean of 8.71 days (1-21 days). The body mass index (BMI) was a mean of 28.5 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Six out of seven patients had one or more predisposing factors: obesity, diabetes, chronic renal failure, corticosteroids and quinolone use.…”
Section: Case Seriesmentioning
confidence: 99%
“…The delay between the injury and surgery was a mean of 8.71 days (1-21 days). The body mass index (BMI) was a mean of 28.5 (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). Six out of seven patients had one or more predisposing factors: obesity, diabetes, chronic renal failure, corticosteroids and quinolone use.…”
Section: Case Seriesmentioning
confidence: 99%
“…Average incidence of injuries among the general population (predominantly US statistics) is shown in orange. [67][68][69][70][71][72] Rates of tendon rupture or disease vary with age and population demographics of geographical location or study human MSCs in the clinical setting. Several studies have also identified heterogeneity in the molecular signature, differentiation capacity, and proliferative potential within individual MSC populations or between MSCs isolated from different sources.…”
Section: Emerging Cell-based Treatments and Engineering Strategiesmentioning
confidence: 99%
“…Muscles are depicted in pink, tendons in grey, and bone in white. Average incidence of injuries among the general population (predominantly US statistics) is shown in orange 67‐72 . Rates of tendon rupture or disease vary with age and population demographics of geographical location or study…”
Section: Applying Lessons From Tendon Development To Augment Existingmentioning
confidence: 99%
“…SQTR is also prevalent in the elderly. An epidemiological study by Aleksi Reito states that by 2013, patients above 60 years old have more than thrice the incidence of SQTR compared with patients below 40 years [3] .…”
Section: Introductionmentioning
confidence: 99%